2019
DOI: 10.3389/fmicb.2019.02592
|View full text |Cite
|
Sign up to set email alerts
|

RAFT-Derived Polymethacrylates as a Superior Treatment for Recurrent Vulvovaginal Candidiasis by Targeting Biotic Biofilms and Persister Cells

Abstract: BackgroundVulvovaginal candidiasis (VVC) is a common infection in need of more effective treatment. Formation of epithelium-associated Candida biofilms and the presence of persister cells are among the major contributing factors to the recurrence of this condition. We have previously developed RAFT-derived polymethacrylates that are effective in killing C. albicans biofilms in vitro. This study aimed to examine the clinical potential of polymethacrylates as antifungals for treatment of recurrent VVC (RVVC).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…More importantly, epithelium-associated biofilms act as a conducive environment that facilitates the formation of persister cells. Using a regimen that kills the bulk of fungal cells with normal susceptibilities, our recent study has successfully isolated persister cells from the vaginal epithelium of mice infected with C. albicans (Wu et al, 2019). These persister cells could not be eradicated by conventional antifungal drugs at very high concentrations and might be the main culprit responsible for the recalcitrance of infections to antifungal treatment (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More importantly, epithelium-associated biofilms act as a conducive environment that facilitates the formation of persister cells. Using a regimen that kills the bulk of fungal cells with normal susceptibilities, our recent study has successfully isolated persister cells from the vaginal epithelium of mice infected with C. albicans (Wu et al, 2019). These persister cells could not be eradicated by conventional antifungal drugs at very high concentrations and might be the main culprit responsible for the recalcitrance of infections to antifungal treatment (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Using a regimen that kills the bulk of fungal cells with normal susceptibilities, our recent study has successfully isolated persister cells from the vaginal epithelium of mice infected with C. albicans (Wu et al, 2019). These persister cells could not be eradicated by conventional antifungal drugs at very high concentrations and might be the main culprit responsible for the recalcitrance of infections to antifungal treatment (Wu et al, 2019). The current study further established a connection between biofilm growth by C. albicans in the vaginal epithelium and the formation of persister cells, supporting a role of Candida biofilm formation in the recurrence of vaginal candidiasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…78 Building from this in vitro study, the optimized guanidine copolymers were investigated as a topical treatment against epithelial-associated C. albicans biofilms in an in vivo murine vulvovaginal candidiasis (VVC) model. 143 The results from this study showed that the polymers displayed negligible local toxicity and resistance to vaginal acidity, and that this formulation outperformed conventional antifungal agents at concentrations 50-fold lower than the over-the-counter concentration of the conventional antifungal drugs. Furthermore, topical treatment using these polymers resulted in fewer persister cell survivors in the fungal biofilms in comparison with conventional antifungals.…”
Section: Antibiofilm Strategies Employing Solution-based Polymer Matementioning
confidence: 73%